Web archiving and archive management / Syahidah Abdul Rahman - Abdul Rahman, Syahidah (2014)
This term paper is discussed about the web archiving and archive management. Web archiving has been gaining interest and recognized importance for modern societies around the world. However, for web archivists it is frequently difficult to demonstrate this fact, for instance, to funders. This study provides an updated and global overview of web archiving. Considering the complexity and large amounts of data involved in web archiving, the results showed that the assigned resources rare scarce. Besides that, this paper also discuss about the current issues and challenges that are face in web archiving and also include the best recommendation and solution about that matter. While for archive management, it is focused on the roles of archivist and the importance of archive institution as a permanent storage for record & and documents to the community.